2006
DOI: 10.1002/jmri.20710
|View full text |Cite
|
Sign up to set email alerts
|

Delayed hyperenhancement patterns in occlusive and reperfused myocardial infarcts during different healing stages

Abstract: Purpose: To investigate delayed hyperenhancement during different healing stages of myocardial infarct with and without reperfusion in a pig model. Materials and Methods:Twelve pigs were studied. Six pigs were subjected to permanent right coronary artery (RCA) occlusion, and the other six were subjected to transient 90-minute RCA occlusion. In vivo MRI including first-pass perfusion and myocardial delayed enhancement (MDE) was performed at four, eight, 12, and 24 hours, and eight days after the artery occlusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 19 publications
3
17
0
Order By: Relevance
“…There were not differences in time to peak (time interval between preinjection and the peak of bolus injection) between scarred and normal myocardium. No perfusion defect was detected on first-pass MRI in 4-week-old scar infarction, which is consistent with prior study demonstrating that the first-pass perfusion defect is detected 4 hours after permanent coronary occlusion and the perfusion defect disappeared 8 days afterwards [13]. These provide strong evidences that two types of CAs can be effectively delivered into scarred myocardium.…”
Section: Discussionsupporting
confidence: 91%
“…There were not differences in time to peak (time interval between preinjection and the peak of bolus injection) between scarred and normal myocardium. No perfusion defect was detected on first-pass MRI in 4-week-old scar infarction, which is consistent with prior study demonstrating that the first-pass perfusion defect is detected 4 hours after permanent coronary occlusion and the perfusion defect disappeared 8 days afterwards [13]. These provide strong evidences that two types of CAs can be effectively delivered into scarred myocardium.…”
Section: Discussionsupporting
confidence: 91%
“…After 8 weeks, there was an excellent agreement between LE and TTC staining. Further data reported LE results for an ischemic time of 90 min being comparable to the LE in group B of the present study [51] . Likewise, the areas of microvascular obstruction decreased in size over time [51] , which was dependent on ischemic time and size of myocardial infarction as seen in previous pharmacological studies [5] .…”
Section: Discussionsupporting
confidence: 68%
“…Further data reported LE results for an ischemic time of 90 min being comparable to the LE in group B of the present study [51] . Likewise, the areas of microvascular obstruction decreased in size over time [51] , which was dependent on ischemic time and size of myocardial infarction as seen in previous pharmacological studies [5] . Microvascular obstruction itself assessed by ceCMRI is clinically of prognostic importance [52][53][54] .…”
Section: Discussionsupporting
confidence: 68%
“…Lee et al have demonstrated that myocardial ischemia caused by the occlusion of a cat coronary artery is hypoenhanced relative to the normal myocardium [22] . Wang et al demonstrated that the nonreperfused occlusive infarct exhibits a first-pass perfusion defect without any delayed hyperenhancement at 4 h after coronary occlusion [23] . Thus, the disappearance of delayed Figure 4.…”
Section: Discussionmentioning
confidence: 99%